GENETIC DIVERGENCE AMONG SUNFLOWER CULTIVARS IN THE NORTH PLATEAU OF SANTA CATARINA STATE - VOGT, Gilcimar Adriano; BALBINOT JÚNIOR, Alvadi Antonio; SOUZA, Adriano Martinho de (Scientia Agraria, 2010)
The objective of this work was to evaluate the genetic divergence among 17 cultivars of sunflower. The experiment was carried out in Papanduva, North Plateau of Santa Catarina State, Brazil, in 2008/2009 cropping season. The experimental design was a randomized block with four replications. The multivariate was used to evaluate the divergence among the cultivars by canonic variable and cluster analysis (UPGMA and Tocher), based on the generalized Mahalanobis Distance (D²). Univariate and multivariate analyses of variance showed differences among cultivars. The cultivars were grouped in tree clusters. The plant height and days until the flowering showed high contribution towards genetic divergence.